Epidemiological analysis of Cassava Mosaic and Brown Streak Diseases, and Bemisia tabaci in the Comoros Islands - Shirima, R.R.; Wosula, E.N.; Hamza, A.A.; Mohammed, N.A.; Mouigni, H.; Nouhou, S.; Mchinda, N.M.; Ceasar, G.; Amour, R.; Njukwe, E.; Legg, James P. (MDPI, 2022)
A comprehensive assessment of cassava brown streak disease (CBSD) and cassava mosaic disease (CMD) was carried out in Comoros where cassava yield (5.7 t/ha) is significantly below the African average (8.6 t/ha) largely due to virus diseases. Observations from 66 sites across the Comoros Islands of Mwali, Ngazidja, and Ndzwani revealed that 83.3% of cassava fields had foliar symptoms of CBSD compared with 95.5% for CMD. Molecular diagnostics confirmed the presence of both cassava brown streak ipomoviruses (CBSIs) and cassava mosaic begomoviruses (CMBs). Although real-time RT-PCR only detected the presence of one CBSI species (Cassava brown streak virus, CBSV) the second species (Ugandan cassava brown streak virus, UCBSV) was identified using next-generation high-throughput sequencing. Both PCR and HTS detected the presence of East African cassava mosaic virus (EACMV). African cassava mosaic virus was not detected in any of the samples. Four whitefly species were identified from a sample of 131 specimens: Bemisia tabaci, B. afer, Aleurodicus dispersus, and Paraleyrodes bondari. Cassava B. tabaci comprised two mitotypes: SSA1-SG2 (89%) and SSA1-SG3 (11%). KASP SNP genotyping categorized 82% of cassava B. tabaci as haplogroup SSA-ESA. This knowledge will provide an important base for developing and deploying effective management strategies for cassava viruses and their vectors.